Studying the changes in the mechanical properties of neutron-irradiated chromium-nickel steels using the “Shear Punch” method - Maksimkin, О.P.; Ruban, S.V.; Nurgaly, Y.Y.; Short, M.P. (Вопросы атомной науки и техники, 2019)
Obtaining mechanical properties of neutron irradiated structural materials is made difficult by the high radioactivity of typical specimen sizes. Developing new mechanical tests which obtain the same properties with far smaller specimen sizes would significantly enhance the speed and safety of performing such tests. In this study, we demonstrate the correspondence in mechanical properties between standard, uniaxial tensile testing and a new “Shear Punch” method, involving the shear-based removal of a small (1 mm) disc of material. Two types of steel, 12Cr18Ni9 and 08Cr16Ni11М3, were irradiated with fast neutrons in the BN-350 reactor up to 23 dpa and shear punch tested between 20…300 °C. Excellent correspondence was found between the 0.2% shear and uniaxial tensile yield stresses, validating this technique as a way to obtain the same mechanical properties with greatly reduced sample size. Представлені і обговорюються результати матеріалознавчих досліджень високорадіоактивних зразків сталі 12Х18Н9, опромінених нейтронами в реакторі ВВР-К, а також зразків сталі 08Х16Н11М3, вирізаних зі стінок чохлів відпрацьованих тепловиділяючих зборок реактора БН-350. Механічно випробували їх за схемою «Shear Punch» на установці, адаптованій для проведення експериментів при температурах в інтервалі 20…300 °С. Була виявлена гарна відповідність між зсувними напруженнями на 0,2% зрушення і одноосного розтягу, яка підтверджує цей метод як спосіб одержання тих же механічних властивостей зі значним зменшенням розміру зразка. Представлены и обсуждаются результаты материаловедческих исследований высокорадиоактивных образцов стали 12Х18Н9, облученных нейтронами в реакторе ВВР-К, а также образцов стали 08Х16Н11М3, вырезанных из стенок чехлов отработавших тепловыделяющих сборок реактора БН-350. Механически испытывали их по схеме «Shear Punch» на установке, адаптированной для проведения экспериментов при температурах в интервале 20…300 °С. Было обнаружено отличное соответствие между сдвиговыми напряжениями на 0,2% сдвига и одноосного растяжения, которое подтверждает эту методику в качестве способа получения тех же механических свойств со значительно уменьшенным размером образца.